Hubungan Masa Kerja Terhadap Keluhan Shoulder Pain Pada Fisioterapis Di Kota Bandung - Elisabeth Dewi Kartika; Trisia Lusiana Amir; Heri Priatna (LPPM Universitas Abdurrab, 2021)
Introduction: Musculoskeletal injuries in physiotherapists appear to have an increasing trend with respect to years of service. A major change from this trend is that musculoskeletal injuries occur in those who have worked for more than 15 years as physiotherapists. This study aims to determine the relationship between working period and complaints of shoulder pain on physiotherapists in the city of Bandung. Methods: This study is a descriptive quantitative study with a cross sectional survey technique. The total sample was 85 physiotherapists (51 females and 34 males) with defined criteria. Samples who complained of shoulder pain were then measured using SPADI (The Shoulder Pain Disability Index). Results: Hypothesis testing using chi square at Î± = 0.05 obtained p = 0.026 with OR (95% CI) = 3.102 (1.12â€“8.61). Shows that there is a relationship between working period and shoulder pain. Physiotherapists with working period > 10 years had a 3,102 fold risk of experiencing shoulder pain complaints compared to those with a working period â‰¤10 years. Conclusion: There is a significant relationship between working period of physiotherapist and complaint of shoulder pain.